The relation between freedom, love, spirit and flesh in Galatians 5:13 - Peter G. Kirchschlaeger (Acta Theologica)
In the Letter of Paul to the Galatian churches the concepts “freedom,” “love,” “Spirit” and “flesh” are important: the semantic dimension of the letter and the theology of the letter strongly depend on these key concepts. Simultaneously, there is a complex relation and interaction between the four concepts. Hence an analysis of the above terms in Galatians 5:13 can contribute to the understanding of the letter. To achieve such understanding, the textual context and the structure of the text are discussed in order to establish a summarising exegesis of 5:1-24, with the focus on an analysis of these terms. This summarising exegesis then forms the basis for a reflection on the relation between “freedom,” “love,” “Spirit” and “flesh” in 5:13.